(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Reflective prism display is a display technology that has potentials in displaying images with fascinating effects. However, the process of creating the display is quite challenging considering the lack of specialized software and bulky hardware setup. In this project, we propose a software toolkit plugin for Unity 3D, called Prismatic, to simplify the process as an alternative over the conventional method of creating a reflective prism display. Adopting the idea from Pepper’s ghost technique, a combination of four cameras facing an object were setup within Unity to produce four viewport renderings of the object, easily projected from a device as small as a smartphone to the size of widescreen TVs. This software toolkit combined with Unity offer simple and centralized control over camera, facets, and object. Prismatic has the potential in assisting apps developer in creating the display such as in showcasing models for education and business purposes.